FEATURES OF THE DEVELOPMENT OF CIVIL LAW REGULATION OF FAMILY RELATIONS IN UKRAINE - Tetiana Fedorenko; Ruslan Rachynskyi (International Journal of Innovative Technologies in Social Science, 2023)
This article examines the peculiarities of the development of civil law regulation of family relations. The main sources of civil law regulation of family relations have been determined: the Civil Code of Ukraine and the Family Code of Ukraine. The definitions of the concepts of family relations and family legal relations are analyzed. It is characterized that civil legislation is applied to family relations in a subsidiary manner, this statement also follows from the provisions of Art. 8 SC of Ukraine. The basic principles and principles on which the Family Law of Ukraine is based are determined.